Analisis Peningkatan Polusi Cahaya Berdasarkan Pembacaan SQM dan Citra Satelit VIIRS tahun 2017 – 2022 di Kota Medan - Putraga, Hariyadi; Raisal, Abu Yazid; Firdaus, Muhammad Dimas; Rakhmadi, Arwin Juli (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
An analysis of light pollution has been carried out based on the reading of a photometercalled Sky Quality Meter (SQM) which shows the level of light pollution expressed in the MPASSreference. This study aims to determine the increase in light pollution in the city of Medan and to findout the implications for astronomical observations there. Light pollution distribution maps data andradiance quantity data are obtained through a platform that presents light pollution mapping and isfurther analyzed with literacy studies. Its Found that the radiance value is proportional to the level ofpollution and is influenced by the population of civilization in Medan from 2017 to 2022 soastronomical observations and phenomena are also decreasing to be visible.